Modelling and managing software federations. - Estublier, J.
Building large software applications from Commerical Off The Shelf tools (COTS) is not an industrial reality so far. This work presents a new approach to solve the different problems found when building a federation of COTS.
Keywords: Software; Software engineering; Interoperability; Design tools and techniques; Modules and interfaces; Management; COTS; Architecture; Federation; Interoperability